Pengaruh Modal kerja dan Tenaga Kerja Terhadap Penjualan Usaha Jajan Tradisional (Studi Kasus Pada Usaha Rumahan di Desa Kelayu Kecamatan Selong Kabupaten Lombok Timur) - Ahda, Falan Yuhlifallohu; Alamsyah (Postgraduate, University of Mataram, 2025)
The purpose of this study was to determine the Effect of Working Capital and Labor on Sales of Traditional Snack Businesses (Case Study on Home Businesses in Kelayu Village, Selong District, East Lombok Regency). The type of research used was a quantitative approach with primary data. The population was 32 traders, with details of 5 semprong snacks, 2 elephant ear snacks, 4 keciput snacks, 3 bangkit snacks, 3 tujeq snacks, 3 tempani snacks, 5 tempeyek snacks, 4 shallot snacks, 1 temberodok snack and 2 sticky rice tepe traders. The data collection techniques used were observation and questionnaires in the form of questionnaires containing questions about Working Capital, Labor and Sales. The analysis tool used was multiple linear analysis using the SPSS version 25 program, which was continued with the godness of fit test (t-test). The results of this study indicate that working capital has a significant effect on sales of traditional snack businesses. Labor has a significant effect on sales of traditional snack businesses. Research findings indicate that working capital is the most important part in running a business, the capital owned will greatly affect sales and business development.